PHOSPHATASE ACTIVITY AND PHOSPHATE SOLUBILITY BY PHOSPHATE SOLUBILIZING RHIZOBACTERIA IN VOLCANIC SOILS OF PANCASARI, BALI - Ketut Dharma Susila; I Made Sudana; Ni Putu Ristiati; I Made Adnyana (International Journal of Biosciences and Biotechnology, 2016)
Phosphatase in the soil was found as extracellular enzymes produced by soil micro-organisms both in acidic or alkaline conditions. Phosphatase is an enzyme complex that plays an important role in deciding soil-bound phosphate bond organic compounds to form orthophosphate which is available to the plant. Mineralization of organic forms into a inorganic-P determined by the ability of these bacteria to produce phosphatase. Therefore, observations of phosphatase activities are important to know how intensely P mineralization process takes place in the soil. Phosphate solubilizing rhizobacteria (PSR) has been widely known to affect mobilization of insoluble inorganic phosphates become available to plants. Although phosphate solubilizing rhizobacteria is widely available in the soil, their activity is usually not strong enough to compete with other bacteria commonly located in the root zone (rhizosphere). That is why, screening of phosphatase enzyme activity and various phosphate solubilizing ability to obtain better strains of bacteria are still needed. This study was conducted to determine the ability of phosphate solubilizing rhizobacteria, its potential as a biofertilizer inoculant and characterize its capacity to dissolve P-insoluble inorganic and produce phosphatase enzymes in the growing medium. Potential phosphate solubilizing rhizobacteria was tested for their ability in vitro using Pikovskaya media containing insoluble forms of inorganic phosphate as a source P. The results of this study indicate that there are some isolates phosphate solubilizing rhizobacteria that are capable of dissolving the insoluble inorganic-P with different abilities. The highest potential successively displayed by isolates TbPP-4.1; BdPP-2.1; and SBPP-1.3 that significantly has the same ability to soluble inorganic phosphate in the soil. The isolates BdPP-2.1 and TbPP-4.1 are significantly higher than the other isolates for producing phosphatase. Both isolates TbPP-4.1 and BdPP-2.1 have the same pontenty as a biofertilizer based on its capacity to mineralize forms of soil organic phosphorus by phosphatase activity.